A parallel Numerical Algorithm For Solving Some Fractional Integral Equations - Mohammed Al-Abrahemee, Khalid Mindeel (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
In this study, He’s parallel numerical algorithm by neural network is applied to type of integration of fractional equations is Abelâ€™s integral equations of the 1st and 2nd kinds. Using a Levenberge â€“ Marquaradt training algorithm as a tool to train the network. To show the efficiency of the method, some type of Abelâ€™s integral equations is solved as numerical examples. Numerical results show that the new method is very efficient problems with high accuracy.